1992
DOI: 10.1182/blood.v79.8.1931.1931
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the mechanism of anagrelide-induced thrombocytopenia in humans

Abstract: Anagrelide is a new therapeutic compound recently demonstrated to have a rapid and selective thrombocytopenic effect in humans. The effects of anagrelide were evaluated in plasma clot and liquid suspension cultures of optimally stimulated normal human peripheral blood megakaryocyte progenitors in order to determine the mechanism of its thrombocytopenic activity. In plasma clot cultures, at clinically relevant, therapeutic concentrations (5 to 50 ng/mL), anagrelide exerted no significant inhibitory effect on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 11 publications
3
19
0
1
Order By: Relevance
“…This apparent selective activity of anagrelide on human megakaryocytopoiesis has been studied in vitro with various concentrations of anagrelide. Our finding of the inhibition of CFU-M growth at supratherapeutic concentrations of anagrelide (Fig 3) is consistent with earlier observations (Mazur et al, 1992). In the latter study a decrease in colony size was also noted only at high concentrations of the drug.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This apparent selective activity of anagrelide on human megakaryocytopoiesis has been studied in vitro with various concentrations of anagrelide. Our finding of the inhibition of CFU-M growth at supratherapeutic concentrations of anagrelide (Fig 3) is consistent with earlier observations (Mazur et al, 1992). In the latter study a decrease in colony size was also noted only at high concentrations of the drug.…”
Section: Discussionsupporting
confidence: 93%
“…Another possibility is that anagrelide might interfere with the intracellular processes that lead to irregular surface events, such as the formation of pseudopods (Leven & Yee, 1987). These observations are similar to those of other investigators who demonstrated that anagrelide induced a shift to the left in the distribution of morphological stages and a decrease in cell size and ploidy of megakaryocytes (Mazur et al, 1992).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous findings have suggested that anagrelide acts primarily on the postmitotic phase of MK maturation (Mazur et al, 1992;Solberg et al, 1997). More recently work by another laboratory has shown that in vivo anagrelide also reduces MK cell numbers (Tomer, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies in humans indicated that anagrelide does not sig-nificantly affect platelet-survival time (Abe et al, 1984) nor that it acts by inducing haematopoietic progenitor cell toxicity (Silverstein et al, 1988). Later on, in vitro studies of human megakaryocytopoiesis suggested that, in vivo, the thrombocytopenic activity of this compound results primarily from an inhibitory effect on the postmitotic phase of megakaryocyte (MK) maturation (Mazur et al, 1992). However, notwithstanding its clinical success and these pioneering cellular studies, unravelling the primary mechanism of action by which anagrelide reduces platelet count has remained elusive .…”
Section: Introductionmentioning
confidence: 99%